The Role of Human Resource Management in Agribusiness Development - Agustina, Eka Santi; Rosalia, Olyvia (Maneggio, 2025)
This study aims to analyze the role of Human Resource Management (HRM) strategies in enhancing productivity and competitiveness in the agribusiness sector, with a focus on the challenges faced by small and medium agribusiness enterprises. The research identifies traditional and modern HRM models applied in agribusiness and evaluates their impact on production outcomes, workforce training, and development. A qualitative descriptive research method is employed, involving interviews with agribusiness practitioners and secondary data analysis from related literature. The findings reveal that effective HRM, particularly through training and employee empowerment, can significantly improve efficiency and productivity in the agribusiness sector. However, small agribusinesses face various challenges in implementing more professional HRM practices, such as limited managerial resources and budgets. The study also highlights the importance of integrating HRM strategies with business objectives and workforce competency development to meet the demands of modern, technology-based agriculture.